Some aspects of cloud burst at the onset of southwest monsoon - RAUF, M.A. (MAUSAM, 2022)
The cloud burst of 10 June 1976 with high rainfall potential at Chittagong and its neighbouring stations at the onset of southwest monsoon is a rare phenomenon that needed thorough studies and investigations. Attempts have been made to study the aerological and synoptic conditions together with the hourly sky conditions, temperatures and pressure variations and wind velocity of Chittagong station for some days before the occurrence of the phenomenon to find out a clue to such a violent phenomena of rainstorms and heavy downpour causing a large scale damage due to landslide and flood in the southeastern part of Bangladesh.